State and Local Intelligence in the War on Terrorism - Riley, K. Jack (RAND Corporation, 2005)
Examines how state and local law enforcement agencies conducted and supported counterterrorism intelligence activities after 9/11. The report analyzes data from a 2002 survey of law enforcement preparedness in the context of intelligence, shows how eight local law enforcement agencies handle intelligence operations, and suggests ways that the job of gathering and analyzing intelligence might best be shared among federal, state, and local agencies.